2019
DOI: 10.1177/0269216318824526
|View full text |Cite
|
Sign up to set email alerts
|

The clinical evaluation of the wish to hasten death is not upsetting for advanced cancer patients: A cross-sectional study

Abstract: Background: An important concern of healthcare professionals when exploring the wish to hasten death with patients is the risk of causing them some type of distress. Aim: To assess the opinion of hospitalized patients with advanced cancer about the proactive assessment of the wish to hasten death. Design: Descriptive, cross-sectional study. Setting/participants: We assessed 193 advanced cancer patients admitted to an oncology ward for the wish to hasten death using a semi-structured clinical interview. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
4
27
0
3
Order By: Relevance
“…Current studies confirm that asking about suicidality causes no harm but may reduce experienced burden and distress. 31 Based on preliminary studies 20,32 these findings can likely be extrapolated to PC. Currently, our clinical guideline is only available for HPs attending the related multi-professional training program.…”
Section: Discussion (Proactively) Addressing Desire To Die Within Trumentioning
confidence: 97%
See 2 more Smart Citations
“…Current studies confirm that asking about suicidality causes no harm but may reduce experienced burden and distress. 31 Based on preliminary studies 20,32 these findings can likely be extrapolated to PC. Currently, our clinical guideline is only available for HPs attending the related multi-professional training program.…”
Section: Discussion (Proactively) Addressing Desire To Die Within Trumentioning
confidence: 97%
“…A recent descriptive study employed an ad hoc semi-structured clinical interview for proactive assessment of a wish to hasten death among advanced cancer patients. 32 Participants did not experience this as distressing, but considered it important regardless of whether they were personally affected. The patients we interviewed indicated that they appreciated the initiation of DD conversations by HPs.…”
Section: Discussion (Proactively) Addressing Desire To Die Within Trumentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies confirm that asking about suicidality causes no harm but may reduce experienced burden and distress. 34 Based on preliminary studies 23,35 these findings can likely be extrapolated to palliative care. Currently, our clinical approach is only available for health professionals attending the related multi-professional training program.…”
Section: Discussion (Proactively) Addressing Desire To Die Within Trumentioning
confidence: 99%
“…If they do, then they may fail to provide 'safe and compassionate care for the dying person'. 5 The paper by Porta-Sales et al 13 in this edition raises whether we should facilitate patients to discuss if they have considered hastening their death. When this was initiated through a semi-structured interview, they found that 98% of their participants reported no distress in talking about and exploring whether they considered hastening their death.…”
Section: How Should Palliative Care Respond To Increasing Legislationmentioning
confidence: 99%